Primary‐care patients’ expectations and experiences of online cognitive behavioural therapy for depression: a qualitative study - Beattie, Angela (Health Expect, 2009)
Objective  To explore expectations and experiences of online cognitive behavioural therapy (CBT) among primary‐care patients with depression, focusing on how this mode of delivery impacts upon the therapeutic experience. Design  Qualitative study, using repeat semi‐structured interviews with patients before and after therapy. The study was conducted in parallel with a randomized controlled trial examining the effectiveness and cost‐effectiveness of online CBT for patients with depression. Participants  Twenty‐four patients with depression recruited from five general practices in southwest England, who were offered up to 10 sessions of CBT, delivered via the internet by a psychologist. Results  Most participants accessed the therapy from their home computer and found this to be a major advantage, in terms of convenience and fitting therapy into their daily routine, with any technical problems quickly resolved. Two key themes regarding expectations and experiences of online CBT were: developing a virtual relationship with a therapist, and the process of communicating thoughts and emotions via an online medium. Online CBT seems to be acceptable to, and experienced as helpful by, certain subgroups of patients with depression, particularly those who are familiar with computers, feel comfortable with writing their feelings down, enjoy the opportunities to review and reflect that written (or typed) communication offers are attracted to the ‘anonymity’ of an online therapeutic relationship and are open to the proactive requirements of CBT itself. However, on‐line CBT may feed into the vulnerability of depressed people to negative thoughts, given the absence of visual cues and the immediate response of face‐to‐face interaction. Conclusions  Online CBT has the potential to enhance care for patients with depression who are open to engaging in ‘talking’ (or typing) therapies as part of their treatment. If online CBT is to be provided via the NHS, it is important to establish patient preferences regarding this mode of delivery and ensure that referral practices are appropriately targeted. The results of our main trial will provide evidence regarding the effectiveness and cost‐effectiveness of receiving therapy via this modality.